Comparison of Oxford Agar, PALCAM and Listeria monocytogenes Blood Agar for the recovery of L. monocytogenes from foods and environmental samples - Pinto, Marlene (2011)
This work had as the main objective a comparison between Listeria monocytogenes Blood Agar (LMBA) and the conventional selective agar media, Oxford and PALCAM, relative to its efficacy in the detection of L. monocytogenes in naturally contaminated food and environmental samples. 173 environmental samples and 272 samples of foods were analysed. A higher sensitivity for detection of L. monocytogenes was verified for LMBA than for PALCAM and Oxford. In LMBA L. monocytogenes could be distinguished from other Listeria spp. by detection of hemolysis. In Oxford and PALCAM this distinction was not possible. The higher growth rate of L. innocua cf. L. monocytogenes in selective liquid media could result in a high number of false negatives (non-detection of the target organism on plates, although its presence was observed by other tests, eg. mini-VIDAS LMO). The need for specific media for the detection of L. monocytogenes in food was confirmed. LMBA could be an alternative medium to use together with PALCAM or Oxford.